FEASIBILITY FOUR WAYS. Issue 1 (14th June 2017) - Hamlin, Alan
Abstract: Both the idea of feasibility and the role that it might play within political theory are controversial. Recent discussions have attempted to specify an appropriate overall conceptualization of feasibility. This essay offers a more nuanced account of a number of interrelated aspects of feasibility and argues for a more realistic view of feasibility. Four aspects of feasibility are identified and discussed: resource feasibility, value feasibility, human feasibility, and institutional feasibility.